2014
DOI: 10.1021/om4006577
|View full text |Cite
|
Sign up to set email alerts
|

Acceptorless Alkane Dehydrogenation Catalyzed by Iridium CCC-Pincer Complexes

Abstract: Iridium complexes of CCC-pincer bis-N-heterocyclic carbenes, including a newly synthesized trifluoromethyl-substituted complex, were examined as catalysts for the acceptorless dehydrogenation of cyclooctane and n-undecane. Up to 103 turnovers were observed for the dehydrogenation of cyclooctane, and up to 97 turnovers were observed for the dehydrogenation of n-undecane. The catalysts showed high initial turnover frequencies, followed by a gradual loss of activity over 24 h. Experiments indicate that this loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 40 publications
3
59
0
1
Order By: Relevance
“…There are, however, reports of alkane dehydrogenation catalyzed by non-phosphine-based pincer-iridium complexes, mainly based on NCN [92,93] and CCC [84,[94][95][96] pincer motifs. Goldberg and coworkers have recently reported the use of a NCN-type pincer-type complex, ( dm Phebox)Ir(OAc) 2 (OH 2 ) (36) for the stoichiometric dehydrogenation of n-octane at 200 C resulting in the formation of ( dm Phebox)Ir(OAc)(H) (61) and octenes (7) [93].…”
Section: ð5þmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, reports of alkane dehydrogenation catalyzed by non-phosphine-based pincer-iridium complexes, mainly based on NCN [92,93] and CCC [84,[94][95][96] pincer motifs. Goldberg and coworkers have recently reported the use of a NCN-type pincer-type complex, ( dm Phebox)Ir(OAc) 2 (OH 2 ) (36) for the stoichiometric dehydrogenation of n-octane at 200 C resulting in the formation of ( dm Phebox)Ir(OAc)(H) (61) and octenes (7) [93].…”
Section: ð5þmentioning
confidence: 99%
“…Chianese and coworkers have investigated the acceptorless dehydrogenation of alkanes catalyzed by CCC pincer-iridium complexes (37)(38)(39)(40)(41)(42) [94]. Complexes 37, 38, and 42 were inactive for acceptorless dehydrogenation under the conditions applied.…”
Section: ð7þ ð8þmentioning
confidence: 99%
“…In addition to simple alkane dehydrogenation, these complexes have been employed for numerous other catalytic transformations of hydrocarbons, including alkane metathesis, 6,8,9,20,[24][25][26] alkyl group metathesis, 27 dehydroaromatization, 19,28,29 alkanealkene coupling reactions, [30][31][32] borylation of alkanes 23 and the dehydrogenation of several non-alkane substrates. 22,33,34 Several pincer motifs more recently explored, such as (CCC)Ir, [35][36][37][38] (PCP)Ru 39-41 , (PCP)Os 42 , and (NCN)Ir 43,44 have been found to show promise for alkane dehydrogenation but as of yet none have proven to be competitive with the well investigated PCP-type iridium-based systems. 26 In early alkane dehydrogenation studies 45 3,3-dimethyl-1-butene (TBE) was found by Crabtree to be a singularly effective hydrogen acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…6 Based on the reported procedures for B, iridium complexes of the N-aryl substituted pro-ligands, 5a and 5b, were obtained as analytically pure materials from reaction between [Ir(COE) 2 Cl] 2 , 1a/1b, and Et 3 N in acetonitrile at elevated temperature, but in low isolated yields of 13 and 11%, respectively (Scheme 3). 18 Under these conditions analysis, by 1 H NMR spectroscopy, of similar reactions carried out with 1c and 1d, however, showed no meaningful evidence for formation of the desired hydride containing products.…”
Section: Iridium Complexes Ofmentioning
confidence: 99%